The Story of Agriculture and Climate Change: The Road We've Travelled - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Agriculture has made slow progress in the international climate change negotiation. The Time To Act is NOW. http://www.agricultureday.org http://www.farmingfirst.org/climate/ Agriculture, Landscapes and Livelihoods Day. 3 December 2012. Doha, Qatar.